2003
DOI: 10.1002/j.2158-1592.2003.tb00038.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodical Usefulness: The U.S. Logistics Educator Perspective

Abstract: Logistics professionals face a challenge today -how to best allocate precious budgetary resources and reading time to a growing array of logistics-related publications. Time-challenged members of the logistics community would benefit from the knowledge of what publications are widely used and found to be of value. This article generates insight into these issues and provides guidance for individuals in search of valuable information tools.Unlike traditional studies of this nature, which base evaluations on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 10 publications
0
77
0
Order By: Relevance
“…Its main drawback is, however, its subjectivity. This second method was used here to examine the index ratings of the main journals on marketing (Hult et al, 1997), logistics (Gibson & Hanna, 2003) and marketing channels (Runyan, 2008), as well as those studies that analyze the multidisciplinary publication preferences of researchers working on SCM (Ferguson, 1983;Fawcett et al, 1995;Kumar & Kwon, 2004;Zsidisin et al, 2007). Appendix I offers a table with the journals proposed by these last authors.…”
Section: Samplingmentioning
confidence: 99%
“…Its main drawback is, however, its subjectivity. This second method was used here to examine the index ratings of the main journals on marketing (Hult et al, 1997), logistics (Gibson & Hanna, 2003) and marketing channels (Runyan, 2008), as well as those studies that analyze the multidisciplinary publication preferences of researchers working on SCM (Ferguson, 1983;Fawcett et al, 1995;Kumar & Kwon, 2004;Zsidisin et al, 2007). Appendix I offers a table with the journals proposed by these last authors.…”
Section: Samplingmentioning
confidence: 99%
“…While JBL occupies rank 7 in our frequency table above, better rankings are achieved when considering the impact and the relative count. For example, when comparing the five most useful journals for U.S. logistics educators, as determined by Gibson and Hanna (2005), against Table 1, JBL received rank one. In addition, we compared our count of global L&SCM articles in each journal to the total number of papers published since 2000 in the respective outlet.…”
Section: Common Themes Investigated In the International Journal Of Omentioning
confidence: 99%
“…The literature study performed is based on a list of relevant journals identified as a compromise between other literature studies performed within the field (Zsidisin, 2003) and evaluations of the usefulness of journals (Gibson & Hanna, 2003). The journals investigated fall in three categories, listed in Table 1 below.…”
Section: Methodsmentioning
confidence: 99%